2010
DOI: 10.1007/s12015-010-9185-7
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cell-extracts Inhibit the Differentiation and Function of Monocyte-derived Dendritic Cells

Abstract: Embryonic stem cells (ESC) possess inherent properties of immune privilege with the capacity to evade allogeneic immune responses. Moreover, ESCs have been shown to prevent immune activation in response to third party antigen presenting cells in vitro and have the capacity to promote allograft survival in vivo. However, clinical use of human ESCs to treat immunological disorders may risk teratoma or ectopic tissue formation. Here, we show that cellular extracts from both human and mouse ESCs retain the immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 47 publications
1
32
0
2
Order By: Relevance
“…We found that mESC derived either by in-vitro fertilization or by nuclear transfer induced profound T-cell hyporesponsiveness in vitro, mainly through soluble factors, and identified prostaglandin-E2 (PGE2) as a potent soluble mediator of ESC-induced immune suppression [29]. Interestingly, others have shown that immune modulation did not require intact hESC, as the cellular protein extract alone was enough to actively inhibit T-cell proliferation in allogeneic MLR by lowering the ability of dendritic cells to stimulate allogeneic T cells [27,30]. This finding suggests that hESC protein extracts could exert an immunomodulatory effect by preventing dendritic cell functional maturation.…”
Section: Key Pointsmentioning
confidence: 99%
“…We found that mESC derived either by in-vitro fertilization or by nuclear transfer induced profound T-cell hyporesponsiveness in vitro, mainly through soluble factors, and identified prostaglandin-E2 (PGE2) as a potent soluble mediator of ESC-induced immune suppression [29]. Interestingly, others have shown that immune modulation did not require intact hESC, as the cellular protein extract alone was enough to actively inhibit T-cell proliferation in allogeneic MLR by lowering the ability of dendritic cells to stimulate allogeneic T cells [27,30]. This finding suggests that hESC protein extracts could exert an immunomodulatory effect by preventing dendritic cell functional maturation.…”
Section: Key Pointsmentioning
confidence: 99%
“…Although other groups reported minimal or no immunogenicity of mouse syngenic iPSC lines and their cellular derivatives (15)(16)(17), these reports highlighted the need for an in-depth characterization of the inherent immunogenicity of hPSC. hESC lines express low levels of MHC class I molecules (18), exhibit immune-privileged properties (19,20), and are rejected in immune-competent mice through a T cellmediated allograft-rejection process (19,21,22); however, the inherent immunogenicity of human iPSC lines has not been examined carefully. In this article, we show that the terminally differentiated gold standard for human immunogenic cells, DC, can be successfully dedifferentiated into the iPSC state using Sendai virus, a nonintegrating RNA virus.…”
mentioning
confidence: 99%
“…Two other reports since then have shown that both undifferentiated and differentiated syngeneic mouse iPSCs are non-immunogenic in vitro and in vivo [45,46]. To date, no studies have examined the immunomodulatory properties of iPSCs even though it is known that ESCs are capable of immunosuppression through multiple mechanisms including expression of arginase I [49,54], prevention of dendritic cell maturation [55] and up -regulation of regulatory T cells [49,56]. When considering the use of iPSCs as an alternative for MSC therapy, this information is critical.…”
mentioning
confidence: 99%